The Impact of Transformational Leadership Style and Organizational Culture on Employee Performance with Organizational Citizenship Behavior as a Moderating Variable in Personnel Agency and Human Resource Development - Sebastian, Aldo (Journal of Current Research In Multidisciplinary, 2024)
This research aims to determine the impact of transformational leadership style and organizational culture on employee performance, with organizational citizenship behavior as a moderating variable. The population in this study was 100 employees. The sample in this study used the census method. The data in this study was obtained through a questionnaire. The analysis model in this research uses an analysis model using structural equation modeling (SEM). Based on the research results, it was found that the transformational leadership style was not proven to have a significant influence on organizational citizenship behavior. Organizational culture was not proven to have an influence on organizational citizenship behavior. Transformational leadership styles are proven to have a positive and significant influence on employee performance. These findings demonstrate the important role of leadership style in creating a motivating and productive work environment. Organizational culture does not have a significant influence on employee performance. Even though the path coefficient value is positive, the results of statistical tests show that this relationship is not significant. This highlights the complexity of the role of organizational culture in the context of its influence on performance. Organizational citizenship behavior (OCB) significantly influences employee performance. This underscores the importance of citizenship behavior in achieving organizational goals and improving overall performance.